Keshalihan Sosial Melalui Pemberdayaan Ekonomi-Sosial Umat pada Masjid Nurul Ashri Yogyakarta - Rachmayanti, Amalia Cahya (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2025)
Mosques play a strategic role as centers for religious, social, and economic activities within the community. This study aims to analyze the implementation of social piety in driving economic and social empowerment at Nurul Ashri Mosque, Yogyakarta. Employing a qualitative approach, primary data were gathered through in-depth interviews, observations, and document analysis, complemented by secondary data from relevant literature and records. The findings reveal that Nurul Ashri Mosque successfully integrates the values of social piety, such as justice, solidarity, and social responsibility, through effective management of zakat, infaq, and sadaqah, along with diverse empowerment programs. These initiatives include skill training, interest-free microcredit provision, social aid distribution, and educational activities. The programs have significantly improved community welfare, strengthened social solidarity, and fostered economic independence among congregants. The mosque also upholds principles of inclusivity and transparency in resource management. Through collaborative approaches and active community engagement, Nurul Ashri Mosque has become a sustainable model of empowerment. This study concludes that integrating religious values with Islamic philanthropic principles enables mosques to serve as agents of meaningful social transformation. The success of Nurul Ashri Mosque offers a replicable model for other mosques to expand their impact on community empowerment across Indonesia.